DISONANSI KOGNITIF PERILAKU MAHASISWA TERHADAP BAHAYA MIKROPLASTIK - Anik Pujiati; Retariandalas; Rahmatulloh (Jurnal Bionatural, 2024)
This research is a quantitative descriptive study which aims to determine students' understanding of microplastics and their relationship with their behavior in using single-use plastics. The method used in this research was a survey technique with a sample of 120 people, namely third semester students at Indraprasta PGRI University. The results of the research show that students' knowledge of microplastics is still very low, namely 90% do not know what microplastics are. This is contrary to the knowledge about the impact of using single-use plastic, most of whom already understand the percentage at 96%. The research results also show that there is cognitive dissonance, namely a condition where cognitively students know that the use of single-use plastic can have an impact on the health of humans and other organisms, but behaviorally they still often and find it difficult to abandon their habit of using single-use plastic packaging.